Automation of a welding rotating device in an automotive industry - Camargo, José Rui; Ferreira, Vicente José Fernandes Costa (Revista Ciências Exatas, 2008)
This work presents an application in the automotive industry which includes the automation of the mechanical welding device. The work station was analyzed in the automotive production during the bodywork welding. This welding device makes the rotation movement that allows the operator welds the bodywork in different positions along the operation cycle. The rotation movement is made through a manual steering wheel and results in ergonomics problems. The main of the automation is to eliminate the manual rotation and replace it for a better solution which improves the ergonomics conditions and the cycle time of the work station.